The Drosophila ortholog of TMEM18 regulates insulin and glucagon-like signaling. Issue 3 (June 2016) - Wiemerslage, Lyle; Gohel, Priya A; Maestri, Giulia; Hilmarsson, Torfi G; Mickael, Michel; Fredriksson, Robert; Williams, Michael J; Schiöth, Helgi B
Abstract : Transmembrane protein 18 ( TMEM18 ) is an ill-described, obesity-related gene, but few studies have explored its molecular function. We found single-nucleotide polymorphism data, suggesting that TMEM18 may be involved in the regulation/physiology of metabolic syndrome based on associations with insulin, homeostatic model assessment-β (HOMAβ), triglycerides, and blood sugar. We then found an ortholog in the Drosophila genome, knocked down Drosophila Tmem18 specifically in insulin-producing cells, and tested for its effects on metabolic function. Our results suggest that TMEM18 affects substrate levels through insulin and glucagon signaling, and its downregulation induces a metabolic state resembling type 2 diabetes. This work is the first to experimentally describe the metabolic consequences of TMEM18 knockdown, and further supports its association with obesity.